Effect of Particle Length to the Quality Particleboard Made from Sorghum Bagasse - Iswanto, Apri Heri; Prabuningrum, Dita Sari; Azhar, Irawati; Supriyanto, Supriyanto (Talenta Publisher, 2018)
The objective of this research was to evaluate the effect of length size particle on physical and mechanical properties of particleboard. Sorghum bagasse was cut into 3, 5, and 7 cm length size. Furthermore, particles were dried until reached of4% moisture content. Amount of 10% urea-formaldehyde (UF) resin used for binding. Hot pressing process conducted in 130ï‚°C temperature for 10 minutes and 30 kg cm -2 pressure. The results showed that thickness swelling (TS) and internal bond (IB) did not fulfill of requirement of Japanese Industrial Standard (JIS) A 5908 (2003). According to all parameters, 3 cm length size of particle was resulting in the best properties.